(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Tubercular lymphadenitis nowadays is the commonest extra pulmonary manifestation of tuberculosis in Bangladesh. Sometimes it causes diagnostic and therapeutic challenge for the clinicians. Occasionally Clinical, laboratory findings and fine needle aspiration cytology (FNAC) is not optimum that creates diagnostic and therapeutic dilemma. FNAC is often inconclusive. Sometimes therapy failed cases and atypical tuberculosis require open biopsy and neck dissection. Objective: To see the effectiveness of lymph node dissection & biopsy for diagnostic purpose and efficacy of the operation in suspected Multi-drug resistant tuberculosis (MDR-TB) for treatment failure due to any reason. Material and Methods: This cross sectional observational study was conducted during the time period of 01st Jan 2014 to 1st Jan 2020 in ENT & Head-Neck Surgery & Pulmonology department, Combined Military Hospital Dhaka on 150 patients who have undergone surgical neck dissection. Results: In this study total number of patients were 216. FNAC was done for all of them and found nonspecific lymphadenitis for 41 cases, lymphoma for 12 cases, sarcoidosis for 08 cases and kikuchi disease for 05 cases. 150 patients were found inconconclusive in FNAC. Inclusion criteria are followings, 1. FNAC is inconclusive & negative 2. Surgery was not done before. Among 150 patients different types of surgery was done like enblock resection, selective neck dissection and modified neck dissection. Histopathologically 06 cases found nonspecific lymphadenitis, 03 cases found lymphoma and 01 case found sarcoid granuloma. 150 cases were found histopathologically tubercular lymphadenitis. They show positive findings in biopsy, caseation necrosis- (100%), C/S +, among the Gene Xpert tests- Gene X-pert (Rif sensitive 83.33%, Rif resistant 16.66%). After completion of anti-tubercular therapy (ATT) (CAT-I HRZE) for total 150 patients, 125 patients were cured and 25 patients were not cured (treatment failure). Out of 25 patients 10 developed multiple cold abscess, 08 developed discharging sinus and 07 had relapse during follow up. 2nd Surgical interventions were done in total 25 patients, 10 TB abscess during ATT (CAT-1 HRZE), 8 discharging sinus and 7 relapse patients along with ATT (CAT-2 SHRZE) and all these patients had no relapse or treatment failure during further follow up. Conclusion: Tuberculous lymphadenitis is best treated with antitubercular medication and in addition surgical neck dissection is more useful in selected cases. So role of surgery is most useful for diagnostic accuracy as well as adjunct to the treatment avoiding prolongation of ATT and noxious side effects of drugs and also to prevent the formation of abscess and sinus. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 86-89